Mestrado profissional em educação nas profissões em saúde: contribuições para o programa a partir dos egressos não concluintes - Ferrari, Carolina Oliveira (2017)
Introduction: The main characteristic of the Professional Masters program is the possibility to approach researching with the routine of professional working, improving the scientific capacity, training professionals to their excellence. Since 2011, the Professional Masters Education program of Health Occupations of PUC/SP campus at Sorocaba, in an interdisciplinary method, meets the need of education of health to fulfill the occupations/education necessity. It’s important to ensure the incoming students success, focusing on curricular evaluation and eventual reasons that lead to a dropout, a complex social phenomenon, defined as an interruption in studies cycle of the student. Object: Discuss the reasons of the MP`s dropouts, analyze the social demographic characteristics of the students that dropout of MPEPS of FCMS of PUC/SP, and describe the personal/professional profile of this students. Material and Methods: This is a cross-sectional study, descriptive, quali-quantity, where the data collection was made between September of 2015 and February of 2016. Of the 100 incoming students between January of 2011 and December of 2014, 21 of these students dropped out. These students that dropped out, responded to a semi structured, self-supporting and online quiz, created by the researcher using the Student`s Integration Postgraduate Model. Results: Twelve (57%) of the students answered the quiz, and those have an average of 37 years old, the majority are female, from the regions near São Paulo. Of these students, nine (75%) will still try to follow an academic career. In an integration of academic and social reasons, the main detected aspects for the dropouts were: financial problems, time mismatch with their jobs and interactions difficulties between the student and the teacher advisor. The average time of most of those students is four semesters, period in which the students had already completed the credits needed in the course`s subjects. Conclusion: The continuity of in-depth studies with non-conclusive graduates may contribute to validate and incorporate new indicators, as well as favor discussions about the determinants of the selection process, identifying the intentions to choose the professional master's degree